2020
DOI: 10.1002/pmic.202000170
|View full text |Cite
|
Sign up to set email alerts
|

Triton X‐114 Fractionated Subcellular Proteome of Leptospira interrogans Shows Selective Enrichment of Pathogenic and Outer Membrane Proteins in the Detergent Fraction

Abstract: The Triton X-114-based solubilization and temperature-dependent phase separation of proteins is used for subcellular fractionation where, aqueous, detergent, and pellet fractions represents cytoplasmic, outer membrane (OM), and inner membrane proteins, respectively. Mass spectrometry-based proteomic analysis of Triton X-114 fractions of proteomic analysis of Leptospira interrogans identified 2957 unique proteins distributed across the fractions. The results are compared with bioinformatics predictions on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…LC-MS/MS analysis of TritonX-114 fractions of L. interrogans serovar Copenhageni strain Fiorcruz L1-130 and subsequent identification yielded 2425 proteins in aqueous fractions, 2646 protein in detergents, and 1684 proteins in a pellet that comprised 2957 unique proteins reported under the ProteomeXchange dataset identifiers PXD009050 and PXD016204 [ 22 ]. The analysis of wash and supernatant identified 837 proteins in wash 851 proteins in the supernatant comprising 1176 unique proteins ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…LC-MS/MS analysis of TritonX-114 fractions of L. interrogans serovar Copenhageni strain Fiorcruz L1-130 and subsequent identification yielded 2425 proteins in aqueous fractions, 2646 protein in detergents, and 1684 proteins in a pellet that comprised 2957 unique proteins reported under the ProteomeXchange dataset identifiers PXD009050 and PXD016204 [ 22 ]. The analysis of wash and supernatant identified 837 proteins in wash 851 proteins in the supernatant comprising 1176 unique proteins ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…The surface proteins were extracted in PBS containing 5 mM MgCl2 that was easily detachable and also had the unique presence of six proteins without shedding out into the supernatant, which showed its sufficiently good binding on the surface of Leptospira . It is also worth noting that 57% of the extracellular proteins found were pathogenic in nature, as was predicted by MP3 tool with a 27.9% rate (826 pathogenic proteins out of the 2957 proteins identified) in the whole proteome of Leptospira [ 22 ]. Even though some of these proteins were found in lower quantities, the possibility of upregulation of the proteins under pathogenic conditions cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conventional proteomics approach using two-dimensional gel electrophoresis (2DE) coupled with matrix assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) [ 10 , 43 ], mainly identifies abundant proteins but inefficiently identifies highly hydrophobic or membrane proteins. In more recent studies, LC-MS/MS, a high-throughput and high-resolution method, was used to identify leptospiral membrane proteins from the samples of subcellular fractionation using Triton X-114 [ 44 , 45 ]. Moreover, LC-MS/MS-based studies and isotope labeling couple revealed protein abundance of leptospires [ 46 ].…”
Section: Discussionmentioning
confidence: 99%